ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO PROFITABILITAS, RASIO LIKUIDITAS DAN RASIO SOLVABILITAS PADA PT HERO SUPERMARKET TBK PERIODE 2015-2024 - Nugroho, Wahyu; Syakhrial (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research analyzes the financial ratios of PT Hero Supermarket Tbk from 2015 to 2024. The ratios analyzed include profitability, liquidity, and solvency ratios. The data is taken from the financial statements of PT Hero Supermarket Tbk for the years 2015 to 2024. The method used in this research is quantitative. The results show that the profitability ratio based on ROA of PT Hero Supermarket Tbk during the period of 2015-2024 only reached an average of -6.36%, and in the last year, it was also only at -0.12%. The ROE ratio has an average ratio value of -21.33%. The liquidity ratio shows that the cash ratio of PT Hero Supermarket Tbk at the beginning of the period was quite good but gradually decreased to a less favorable condition, with an average ratio level of only 7.71% during the 2015-2024 period, and the CR in the last year only touched 50,56%. The quick ratio also experienced fluctuations with a low ratio capability from year to year, with an average value of 38.29%. In the solvency ratio, the calculation results in an average debt to assets ratio of 54.25% and a debt to equity ratio of 218.54%